2018
DOI: 10.1108/ijchm-10-2016-0596
|View full text |Cite
|
Sign up to set email alerts
|

Towards green experiential loyalty

Abstract: Purpose This paper aims to test the relationships among the experiential quality dimensions, the green relationship quality dimensions, environmental friendliness, green support, green desire and green experiential loyalty in a green bed & breakfast (B&B) context. Design/methodology/approach The data used in this study are based on a sample of 517 customers staying at one green B&B in Yilan County of Taiwan. The predicted relationship is tested using structural equation modeling. Findings The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 82 publications
1
32
0
Order By: Relevance
“…In the quest to preserve lasting commercial relationships with guests, literature has identified several variables that influence guest loyalty, such as, among others, trust and satisfaction, which are deemed to be determinants in the maintenance of long-term relationships between hotels and their guests [10][11][12][13][14]. In this vein, the value-satisfaction-loyalty chain has been supported by previous research in tourism and hospitality [15].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In the quest to preserve lasting commercial relationships with guests, literature has identified several variables that influence guest loyalty, such as, among others, trust and satisfaction, which are deemed to be determinants in the maintenance of long-term relationships between hotels and their guests [10][11][12][13][14]. In this vein, the value-satisfaction-loyalty chain has been supported by previous research in tourism and hospitality [15].…”
Section: Introductionmentioning
confidence: 85%
“…Literature has shown that trust and satisfaction are closely related to each other [10,11,14,70,71]. For example, in their studies on restaurant customers, authors in [70,71] demonstrated that trust represents an important antecedent for their satisfaction with the company.…”
Section: Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations